Tensile strength and histological changes of abdominal aorta of malnourished rats - Yoshida, Winston Bonetti [UNESP]; Müller, Sérgio Swain [UNESP]; Carvahlo, I. [UNESP]; Fabris, Viciany Erique [UNESP]; Naresse, Luiz Eduardo [UNESP]; Maffei, Francisco Humberto de Abreu [UNESP] (SAGE Publications, 1995)
The resistance of the abdominal aorta of rats after 6, 7 and 8 weeks of malnutrition, compared with control animals, was evaluated by longitudinal tensiometry. Weakness of this vessel in malnourished rats was demonstrated; microscopic examination of the aorta stained by Masson, Calleja and hematoxylin-eosin methods showed a decrease in amorphous ground substance and an increase in the width of elastic laminae. There was no visible alteration either in the endothelial lining layer or in the smooth muscle fibers. Such alterations of the aorta are, to the authors' knowledge, the first reported modifications in the peripheral vasculature after malnutrition.
Keywords: Aorta; Blood vessels; Collagen; Protein-calorie malnutrition; abdominal aorta; animal experiment; aorta wall; controlled study; nonhuman; priority journal; protein calorie malnutrition; rat; tensile strength; vascular resistance; Animal; Aorta, Abdominal; Body Weight; Elastic Tissue; Protein-Energy Malnutrition; Rats; Rats, Wistar; Tensile Strength